ON THE STUDY AND RESEARCH OF THE CREATIVE HERITAGE OF ZAHIRIDDIN MUHAMMAD BABUR - Rahmonali Hasanov (Galaxy International Interdisciplinary Research Journal, 2023)
This article provides information about, the material and spiritual wealth of Zahiriddin Muhammad Babur and the Babur dynasty, the scientific and creative heritage of Zahiriddin Muhammad Babur, in particular, the "Boburnoma", the researches conducted by our republican and foreign scientists and their comparative analysis are described.